Targets of 72Germanium for in-beam gamma-ray spectroscopy - Kindler Birgit; Hübner Annett; Lommel Bettina; Reckziegel Anita; Saifulin Maxim; Steiner Jutta; Yakusheva Vera (EPJ Web of Conferences)
At the Experimental Storage Ring ESR at GSI experiments on the investigation of the isolated nuclear two-photon decay were performed [1]. For a better understanding, complementary experiments were planned at the TANDEM accelerator at the University of Cologne, Germany. For these experiments targets from enriched 72Ge on a thin titanium backing as well as self-supporting targets were needed. As we had only scarce material available, thermal evaporation in a close evaporation geometry was the method of choice. 72Ge-targets in a thickness range of 350 μg/cm² - 370 μg/cm², self-supporting and with titanium backing, were obtained. We report on the target production and on first results of their application in the experiment.